The political economy of trade policy : papers in honor of Jagdish Bhagwati - Bhagwati, Jagdish N., 1934-; Feenstra, Robert C.; Grossman, Gene M.; Irwin, Douglas A., 1962- (MIT Press, 1996)
This collection of papers by colleagues and former students celebrates the profound impact that Jagdish Bhagwati has had on the field of international economics over the past three decades. Bhagwati, who is the Arthur Lehman Professor of Economics at Columbia University, has made pathbreaking contributions to the theory of international trade and commercial policy, including immiserizing growth, domestic distortions, economic development, and political economy. His success and influence as a teacher and mentor is widely recognized among students at both MIT and Columbia, and as founder of the Journal of International Economics, he has encouraged research on many questions of theoretical and policy relevance. The political economy of trade policy, Bhagwati's most recent area of interest, is the theme of this collection, which addresses salient topics including market distortions, income distribution, and the political process of policy-making.